Upaya Meningkatan Kemampuan Menyimak Melalui Metode Bercerita Menggunakan Boneka Karakter - Yosigite, Yosigite; Sari, Rika Partika; Haryono, Mimpira (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study was to determine efforts to improve listening skills through storytelling methods using character dolls at PAUD Mutiara Rabbani Bengkulu City. This research is a Classroom Action Research (PTK) or also called Classroom action research with the procedures used in the form of cycles. The subjects of this study were group A children at PAUD Mutiara Rabbani Bengkulu City, totaling 20 children. The research was conducted in two cycles of two meetings. Data analysis was carried out in qualitative and quantitative descriptions with the emphasis used to determine the improvement of the process expressed in a predicate, while quantitative analysis was used to determine the improvement of results using percentages. The results of improving listening skills through storytelling methods using character dolls at PAUD Mutiara Rabbani in cycle I meeting to I with a percentage of 39.75%, in cycle I meeting to II with a percentage of 48.75%, cycle II meeting to I with a percentage of 62% and cycle II meeting to II with a percentage of 76.25%. The research concluded that using character dolls can improve listening skills in children at PAUD Mutiara Rabbani Bengkulu City, as evidenced in cycle II meeting II there was an increase with the results of the achievement percentage of 82.25% with very good developing criteria (BSB)..